2022
DOI: 10.2485/jhtb.31.1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Change in Solubility over Time of the Bioactive Material Amorphous Calcium Phosphate and Precipitation of Hydroxyapatite

Abstract: In this study, we immersed amorphous calcium phosphate (ACP) powder in biochemical buffer solutions and performed analysis of its solubility and phase transformation of the precipitate. After preparing ACP powder that contains no impurities, we used 4-(2-hydroxyethyl)-1-piperazinetethanesulfonic acid (HEPES) buffer, one of the good buffers, as a buffer solution and measured the amount of calcium ions eluted from ACP and other calcium phosphate crystals. ACP was immersed in the buffer solution at 5°C, 20°C, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The synthetic ACP and HEPES buffer (pH 7.4) were mixed in the proportion of 1:2,000 and incubated at 37ºC for 30 minutes, after which the reaction was halted by treating the centrifuged precipitate with 100% ethanol, and the ethanol was evaporated at room temperature to obtain HAP powder. The precipitate obtained by this method is HAP that has undergone a phase transition from ACP over a short time period, and it has been confirmed to be HAP by X-ray diffraction 2) .…”
Section: Effect On Dentin Of Ions Eluted From Acpmentioning
confidence: 84%
See 2 more Smart Citations
“…The synthetic ACP and HEPES buffer (pH 7.4) were mixed in the proportion of 1:2,000 and incubated at 37ºC for 30 minutes, after which the reaction was halted by treating the centrifuged precipitate with 100% ethanol, and the ethanol was evaporated at room temperature to obtain HAP powder. The precipitate obtained by this method is HAP that has undergone a phase transition from ACP over a short time period, and it has been confirmed to be HAP by X-ray diffraction 2) .…”
Section: Effect On Dentin Of Ions Eluted From Acpmentioning
confidence: 84%
“…We have previously reported that HAP is deposited within 15 minutes at an ACP:HEPES ratio of 1:2,000 (we./wt. ratio) 2) . However, a mixture of ACP and HEPES with a P/S ratio of 1:2,000 is practically liquid, and it would therefore be highly likely to run out of the cavity immediately after filling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation